People, wagons and horses in front of Northern Navigation Co.'s passenger and freight depot, Dawson, Yukon Territory, ca. 1904 - Nowell, Frank H., 1864-1950 (1904)
Caption on image: 6275 On verso of image: Northern Navigation Co.'s passenger and freight depot, Dawson, Y.T. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number